VISUAL ANALYSIS AND GENERATION Z’S INTEREST IN YOU-C 1000 ADVERTISING VIDEO - Anindya Pradipta Hutami; Sani Ratna Amelia; Nerissa Nadhrota Maulviyah; Achmad Ibrahim Mashudi; Putu Chrisma Dewi; Putu Chris Susanto (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTEntering 2020, one of the trends that marketers should pay attention to is the growinginfluence of Generation Z. The new generation that will dominate the market after themillennial segment is Generation Z. Video is believed to be a medium that is quite influentialin building bonds with the audience. This study aims to analyze the use of video visualmedia in increasing Generation Z's interest in the products offered and to understandGeneration Z's level of interest in video advertising as a visual medium. The method used inthis action is a qualitative grounded theory model that analyzes abstract theories aboutprocesses, actions, or interactions based on the views of participants. In addition, it alsouses the SWOT analysis method which is used to monitor and evaluate research conductedboth from external and internal factors for a particular purpose. In this study there are twostages, the first is the interview stage to determine the response of Generation Zparticipants who tend to be interested in the visualization of advertisements for the You-C1000 Vitamin Drink product. Then in the second stage, namely analyzing the results of theinterview to find out the participant's response to the product ad video. The results showedthat the visual video media succeeded in increasing the interest of participants fromGeneration Z to watch advertisements until they ran out.Keywords: Generation Z, Interest, Advertising, Video, Grounded theory